A numerical investigation of SBLOCA scenario in nuclear heating reactor. Issue 8 (3rd August 2019) - Lu, Meng; Xie, Heng
ABSTRACT: Small break loss of coolant accident (SBLOCA) is one of the most important severe accidents in nuclear heating reactor. Nuclear heating reactor designed by Tsinghua University, whose primary loop is integrated layout and designed without main pump. The initial water volume in the reactor vessel is important to determine whether the reactor will be cooled or not as no safety injection system is designed for coolant makeup during the whole scenario. This paper simulates SBLOCA in nuclear heating reactor based on RELAP5. Transient behavior of relevant thermal parameters is specifically analyzed. Moreover, investigation also has been made on SBLOCA scenario based on different residual heat removal correlations and found the long-term residual heat removal capacity is decisive in determining the loss of coolant. The mathematical form of residual heat removal correlation is specifically deducted and can be widely applied to different situations. The envelope line that differentiates the region whether the core is safe or not under different maximum PRHRS capacity is also given.